Impact of Digital Payment Adoption on Customer Satisfaction: An Empirical Study in the Indian Banking Sector - C. Sree Naga Pranavi, Thatiparthi Naga Malleswari; Gunti Alisha, Syed M. Parveen, Lanke.Srilatha (Journal of Informatics Education and Research, 2025)
The rapid adoption of digital payment systems has transformed the Indian banking sector by redefining service delivery, transaction efficiency, and customer interaction. With the expansion of Unified Payments Interface, mobile banking, internet banking, and digital wallets, customer expectations regarding speed, convenience, security, and reliability have significantly increased. This study empirically examines the impact of digital payment adoption on customer satisfaction in the Indian banking sector by focusing on four key dimensions: ease of use, transaction security, service reliability, and speed of transactions. Primary data were collected from 100 banking customers across public and private sector banks using a structured questionnaire. The study employs regression analysis and one-way ANOVA to test the proposed hypotheses. The findings reveal that ease of use and transaction speed have a strong positive influence on customer satisfaction, while transaction security significantly affects trust and continued usage. Service reliability emerged as a critical determinant of long-term satisfaction. The study concludes that effective digital payment adoption significantly enhances customer satisfaction when supported by robust security mechanisms and user-friendly interfaces. The findings provide valuable insights for banks, policymakers, and fintech stakeholders aiming to strengthen India’s digital payment ecosystem